2014
DOI: 10.1103/physrevd.89.064047
|View full text |Cite
|
Sign up to set email alerts
|

From Brans-Dicke gravity to a geometrical scalar-tensor theory

Abstract: We consider an approach to Brans-Dicke theory of gravity in which the scalar field has a geometrical nature. By postulating the Palatini variation, we find out that the role played by the scalar field consists in turning the space-time geometry into a Weyl integrable manifold. This procedure leads to a scalar-tensor theory that differs from the original Brans-Dicke theory in many aspects and presents some new features.Comment: 21 page

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(120 citation statements)
references
References 63 publications
5
114
0
1
Order By: Relevance
“…Adopting the Palatini procedure, it can be shown that the variation of the action (2) with respect to the affine connection yields [18] …”
Section: The Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting the Palatini procedure, it can be shown that the variation of the action (2) with respect to the affine connection yields [18] …”
Section: The Formalismmentioning
confidence: 99%
“…These may be regarded as scalar-tensor theories in which the scalar field plays a clear geometric role 1 . In the present paper, we shall consider a more recent geometrical approach to scalar-tensor theory [18]. This approach starts by considering the action of Brans-Dicke theory and introduces the space-time geometry from first principles, which is done by applying the Palatini formalism.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above, this leads to the conclusion that the Universe, as modeled by GR, must necessarily have had a beginning starting from a singular state. Let us now consider some different scenarios offered by two alternative gravitational theories, namely, the Novello-Oliveira-SalimElbaz's theory (N) [17,34] and a recent geometrical approach to scalar-tensor theory (GST), both inspired by the idea that space-time can be described by Weyl integrable geometry [35].…”
Section: Theorem 52 Letmentioning
confidence: 99%
“…By applying the Palatini variational method, one obtains the Weyl integral compatibility condition [35],…”
Section: Geometrical Scalar-tensor Theorymentioning
confidence: 99%
“…This is somehow a reminiscence of the quantum effects described by the Rastall equation. Other geometrical frameworks, like Weyl geometry, may lead to equations similar to the ones in Rastall gravity [8,9].…”
Section: Introductionmentioning
confidence: 99%